Destiny in the Desert The road to El Alamein - the Battle that Turned the Tide - Dimbleby, Jonathan (Profile book, 2012)
It was the British victory at the Battle of El Alamein in November 1942 that inspired one of Churchill's most famous aphorisms: 'This is not the end, it is not even the beginning of the end, but it is, perhaps, the end of the beginning'. And yet the true significance of this iconic episode remains unrecognised. In this thrilling historical account, Jonathan Dimbleby describes the political and strategic realities that lay behind the battle, charting the nail-biting months that led to the victory at El Alamein in November 1942. It is a story of high drama, played out both in the war capitals of